INFLUENCE OF PLANNED EXERCISE PROGRAMME ON MUSCLE MASS OF ELDERLY AGED MALE - K.M, Thomas (ShodhKosh: Journal of Visual and Performing Arts, 2023)
As individuals age, they experience a gradual decline in muscle mass and strength, a condition known as sarcopenia. This decline is often associated with reduced mobility, increased risk of falls, and a decreased quality of life. The purpose of this study was to investigate the influence of a structured, planned exercise program on the muscle mass of elderly males aged 60 and above. This research investigated the influence of planned exercise programme on muscle mass of elderly aged male.